Impact Analysis of Marine Affairs Decentralization Policy on Fishermen's Socio-Economic Conditions in Alor Regency - Rahmad ZAINUDIN; David B.W. PANDIE; Laurensius P. SAYRANI (PT Keberlanjutan Strategis Indonesia, 2023)
This study explains the impact of the demolition design on Alor fishermen's socio-economic conditions. This research was done in Alor, East Nusa Tenggara. This study focuses on the transition in managing government affairs in the budget sector from the District Government to the Provincial Government. The author uses Wolman's opinion in Faquet regarding repeal in the distribution of government affairs as an analytical tool. This theory classifies government affairs into two aspects: efficiency and governance management. This study is a qualitative study involving interviews, documentation, and observation. Miles and Huberman's data analysis approaches were employed to validate study outcomes. Based on economies of scale, the study reveals that the demolition design has no impact on the socio-economic conditions of Alor fishermen. Based on externalities (both positive and negative), the study shows that more negative impacts arise from the arrival of people outside the district (migrant fishermen) in terms of fishing because they dominate more in terms of supervision. In contrast, immigrant fishermen are less controlled and supervised strictly. Other dominance covers the market and areas in Alor Regency. The analysis shows that the provincial government has above-average economic (potential) and administrative capabilities for management quality. Human resources, infrastructure, and budget are still issues. The analysis shows that the provincial government has above-average economic (potential) and administrative capabilities for management quality. Human resources, infrastructure, and budget are still issues. Fortunately, the provincial government is still helped by the partnership system